2022
DOI: 10.1002/jcla.24588
|View full text |Cite
|
Sign up to set email alerts
|

Multiple diagnostic methods for mucormycosis: A retrospective case series

Abstract: Background Mucormycosis is a rare invasive fungal disease with high mortality. Early diagnosis and targeted drugs are crucial to improving clinical outcomes. Methods We searched the electronic hospital database of the First Affiliated Hospital of Zhejiang University School of Medicine for adult patients with mucormycosis between 2000 and 2021. Demographic, clinical, treatment, and outcome data were collected and compared with the data in the relevant literature. Results Eleven cases of mucormycosis—four of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Most of the current studies on the diagnosis of IFD by mNGS are clinical case reports (Chen et al, 2021;Wang et al, 2022;Cui et al, 2022;Hu et al, 2022). Several studies have focused on the diagnosis of pulmonary infections by mNGS, Peng et al reported on 60 patients with suspected pneumonia in severe immunodeficiency and analyzed the diagnostic efficacy of mNGS versus CMTs for pneumonia (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current studies on the diagnosis of IFD by mNGS are clinical case reports (Chen et al, 2021;Wang et al, 2022;Cui et al, 2022;Hu et al, 2022). Several studies have focused on the diagnosis of pulmonary infections by mNGS, Peng et al reported on 60 patients with suspected pneumonia in severe immunodeficiency and analyzed the diagnostic efficacy of mNGS versus CMTs for pneumonia (Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current studies on the diagnosis of IFD by mNGS are clinical case reports ( Chen et al., 2021 ; Wang et al., 2022 ; Cui et al., 2022 ; Hu et al., 2022 ). Several studies have focused on the diagnosis of pulmonary infections by mNGS, Peng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvement in early recognition of the disease, diagnosis remains challenging, which results in delayed appropriate treatment and poor outcomes [55]. Considerable progress has been made in the development of various PCR diagnostics in MCR.…”
Section: Microbiological Diagnosis Of Mucormycosismentioning
confidence: 99%
“…Metagenomic next-generation sequencing was the main method used to diagnose MCR (67%) or colonization (22%) with Lichtheimia in a series of patients with underlying hematological malignancy, solid organ transplant, pulmonary disease, or trauma [61 ▪ ]. In another series, samples from patients with pulmonary MCR were analyzed by using metagenomic next-generation sequencing and culture; in one patient with disseminated infection only metagenomic next-generation sequencing confirmed the diagnosis [55]. Zhang and colleagues described two patients with hematologic malignancies treated with chemotherapy and targeted therapy whose courses were complicated one by nasal MCR caused by Lichtheimia ramosa and the other by cutaneous infection with Mucor irregularis [62].…”
Section: Microbiological Diagnosis Of Mucormycosismentioning
confidence: 99%